D-Glucose based synthesis of proline–serine C–C linked central and right hand core of a kaitocephalin-a glutamate receptor antagonist. Issue 99 (23rd September 2015) - Markad, Pramod R.; Rohokale, Rajendra S.; Pawar, Nitin J.; Dhavale, Dilip D.
Abstract : Synthesis of the proline–serine core of kaitocephalin starting fromd -glucose, utilizing the Jocic–Reeve and Corey–Link reaction sequence as key steps. Abstract : The synthesis of the proline–serine core of kaitocephalin1 was accomplished starting fromd -glucose wherein, C2 ofd -glucose provided the carboxylic acid functionality of serine; while the amino- and β-hydroxy groups of the serine fragment were amenable from the C3 and C4 hydroxy groups of sugar. The key intermediate to construct substituted proline with the appropriate quaternary carbon framework of the target molecule was constructed using the Jocic–Reeve and Corey–Link reaction sequence with the desired stereochemistry from the C5-centre ofd -glucose.